PSS-STUDY: PSS-Study: An Exploration of Physiotherapy Student-Perceived Stress and the Related Coping Strategies whilst on Placement - Bennion, Jacqueline; Symmons, Trystan; Shearman, Ian; Holloway, Charlotte; Kain, Richard (International Journal of Practice-based Learning in Health and Social Care, 2020)
Evidence exploring stress and coping strategies amongst physiotherapy students within clinical practice is lacking. The aim of this study is two-fold: to identify common stressors and coping strategies of BSc and MSc UK physiotherapy students on clinical placement; to explore the relationship between these stressors and coping strategies, and demographics of age, gender and year of study. This cross-sectional study recruited a convenience sample. Participants completed a five-part closed questionnaire. Seventy-seven questionnaires were returned. Frequency counts identified common stressors and coping strategies (%). Chi-squared test analysis identified correlations between variables. Odds ratio analysis highlighted strength of associations. Common stressors: lack of practical skills (58.4%); participants’ perceived expectations of required knowledge (57.1%); time demands (55.8%). Common coping strategies: talking to a friend in the same year of study (79.2%); exercise (68.8%). Lack of support from university/clinical staff (p = 0.04), time demands (p = 0.03) were statistically significant stressors in relation to age. Talking to a friend in the year above was a statistically significant coping strategy (p = 0.008) for male students. Talking to a clinical educator/ward staff was a statistically significant coping strategy in relation to year of study (p = 0.035). Certain stressors were experienced more by second-year BSc and second-year MSc cohorts than the third-year BSc cohort. These findings provide awareness of students who potentially require support in managing stress.